Nursing in the immediate care of the victim of sexual violence (Research, Society and Development, 2020)
Objective: to analyze in the main literature how the nurse's performance should be in the face of emergency care for the victim of sexual violence, identifying the main challenges in the immediate care of this victim. Methodology: it is an integrative literature review, with a qualitative approach and descriptive characteristics of the theme in question. The survey was carried out from February to November 2019, by the Virtual Health Library, in the databases: Lilacs, Medline, Bdenf and Ibecs, using the descriptors: Sexual violence, AND Violence against women, AND Nursing care. Another search was carried out on the Google Academic virtual library platform, with the descriptors: Sexual violence ”AND“ Nurse ”AND“ Notification. The time frame of both searches was from 2014 to 2018. The initial survey was 659 articles. After complete analysis, there were 14 articles that made up the final sample of this research. Results: the nurse is responsible for actions of identification, prevention, guidance, assistance to the victims and notification of the incident. Using as a tool the nursing process with anamnesis, physical examination, diagnosis, planning, implementation and evaluation of nursing. The latter also has the responsibility of not forgetting the ethical, moral and legal precepts that involve cases of violence. Conclusion: The studies analyzed showed numerous challenges in the immediate care of victims of sexual violence, such as the scarcity of materials and supplies, inappropriate places for care, which must be individualized and reserved so as not to expose intimacy and respect the patient's dignity. As well as non-physical barriers such as the lack of human resources, which generates work overload for the team.